(untitled) (Medico Legal Update, 2021)
Prostate cancer or carcinoma of prostate is the development of cancer in the prostate a gland in the male reproductive system. This is a cross sectional, hospital based study. This study was carried out at the Oncology Center in Kirkuk City- Iraq from the 1st of February 2020 to the end of June 2020. A verbal consent was taken from each Men included in this study whether considered as a case or control. Sixty _ Seven men with prostatic cancer were screened to participate in the present study. Men with prostatic cancer attended to Oncology Center were enrolled in this study. The diagnosis of prostate cancer was made by the patient’s file contain information about his state after take agreement from each Men included in this study, that is mean that the diagnosis of prostate cancer was according to discussion of the oncologist . Men ages were between 52 to 89 years, and they were from the center and periphery of Kirkuk City. Forty-Seven Men with prostatic cancer were considered as a study group, three Men did not meeting the inclusion criteria and 17 Men refuse to participate in this study due to the personal reasons. Forty apparently healthy Men without prostatic cancer and with negative family history. Each Men with benign tumor, benign prostatic hyperplasia or prostatitis diseases were excluded from this study. By using a sterile disposable syringe, 5 ml of venous blood sample was drawn from the vein of each Men at morning and was kept into disposable gel tube and allowed to clot for(2hour) at room temperature, then each sample was centrifuged at 6000 rpm for 10 minutes to obtain serum. The serum was aspirated by mechanical micropipette and transferred into clean Eppendorf tubes which labeled with number, then put this Eppendorf tubes in urine cups for safety and addition more information like name, date, number and stored at - 20 0 C until the time of estimation. Serum of the patients and controls had assay for: Human IDO1 (Indoleamine 2,3-dioxygenase 1) and Human acid phosphatase/prostate by ELISA. The study demonstrated that, the rate of prostate cancer occurrence was increased with age and majority of patients were belonged to the age group (70-79 years). The study also showed non-significant difference between patients and control regarding their BMI mean (27.36±5.16 vs. 27.24±3.34kg²) respectively. The study showed that, serum level of IDO1 enzyme was elevated significantly (P<0.01) in prostate cancer patients (11.74±0.28 pg/ml) as compared with healthy control group (4.78±0.15 pg/ml). The study showed that, the highest mean of PAP enzyme was recorded in prostate cancer patients (0.111±0.075 pg/ml) as compared with healthy control group (0.069±0.024 pg/ml). The difference was highly significant (P<0.01), Table 3. The study showed positive correlation between PAP enzyme and stage of prostate cancer (r: 0.34). The study showed positive correlation between IDO1 level and stage of prostate cancer (r: 0.62). The study showed negative correlation between IDO1 level and PAP level in prostate cancer patients (r: -0.22).